2019
DOI: 10.3390/metabo9040080
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Lipidomics of Alveolar Lavage Fluid in Mice Based on Ultra-High-Performance Liquid Chromatography Coupled to Hybrid Quadrupole-Exactive Orbitrap Mass Spectrometry

Abstract: Surfactant lipid metabolism is closely related to pulmonary diseases. Lipid metabolism disorder can cause lung diseases, vice versa. With this rationale, a useful method was established in this study to determine the lipidome in bronchoalveolar lavage fluid (BALF) of mice. The lipid components in BALF were extracted by liquid–liquid extraction (methanol and methyl tert-butyl ether, and water). Ultra-high-performance liquid chromatography coupled to hybrid Quadrupole-Exactive Orbitrap mass spectrometry was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…In the small airways, surfactant maintains airway patency [1,2]. The study of surfactant has seen a renewed interest in the last decade, partly owing to the availability of new and sensitive techniques like mass spectrometry [3,4] Environmental and genetic factors can originate surfactant insufficiency [5]. Premature birth leads to surfactant deficiency in neonates and cause respiratory distress syndrome (RDS) for which exogenous surfactant therapy is routinely administered [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…In the small airways, surfactant maintains airway patency [1,2]. The study of surfactant has seen a renewed interest in the last decade, partly owing to the availability of new and sensitive techniques like mass spectrometry [3,4] Environmental and genetic factors can originate surfactant insufficiency [5]. Premature birth leads to surfactant deficiency in neonates and cause respiratory distress syndrome (RDS) for which exogenous surfactant therapy is routinely administered [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings confirmed that the main flavone constituents in QF, such as Quercetin and Luteolin, could inhibit RSV replication by directly blocking viral adhesion or modulating microRNA-related signaling pathways ( Wang S. et al, 2020 ; Lopes et al, 2020 ). Although there was no literature reporting direct links between RSV and Kaempferol, Naringenin, or Isorhamnetin, these compounds are reported to play critical roles in antiviral and anti-inflammatory procedures by reducing viral replication, inhibiting inflammatory cytokines, and eliminating free radicals in respiratory tract viral diseases ( Yang et al, 2019 ; Huang YF. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…If p ( k ) ≤ k α/ r for all 1 ≤ k ≤ r (i.e., the case s = r ), the hypothesis is rejected. A p value of 0.05 and an FDR of 0.05 (hydrophilic metabolites) 35 or 0.2 (lipophilic metabolites) 36 were set as statistical significance levels.…”
Section: Methodsmentioning
confidence: 99%